The Social Discount Rate, Consumption, and Capital - Levhari, D.; Liviatan, N.; Luski, I. (Quarterly Journal of Economics, 1974)
I. Introduction, 117. — II. The simple model (continuous time), 117. — III. The discrete production model and the Golden Rule, 119. — IV. Discounting and the optimal stocks of capital, 121.